Screening for Peripheral Arterial Disease in Patients with Coronary Artery Disease Using Ankle-Brachial Index - HajiraSarwar, Inamullah Shah, Sajida Shah,Eitezaz Ahmad Bashir (Journal of Rawalpindi Medical College, 2018)
Background : To screen for presence of peripheral arterial disease (PAD) in coronary artery disease (CAD) patients using ankle- brachial index (ABI). Methods: In this descriptive cross-sectional study patients (n=310) above the age of 40 years of both genders, admitted with diagnosis of coronary arterial disease were included. Smokers and patients with hyperlipidemias, diabetes mellitus, or ankle brachial index (ABI) >1.5 were excluded. Patients with ABI of less than 0.9 in one or both lower limbs were diagnosed to have PAD. Results : Out of 310 patients, 26.77% (n= 83) had ABI < 0.9. Majority of these patients (85.1%) were asymptomatic. ABI was able to detect PAD in all these patients. There was no statistical difference in prevalence between genders. Conclusion: Arterial brachial index is able to dectect peripheral arterial disease in patients with coronary artery disease .